(untitled) (Philology, 2023)
The topic of the present article explores the place of the fairy tale in foreign language learning for adults. The research aims to reveal the rich potential of the fairy tale for the successful training of foreign students in the Bulgarian language in foreign universities. Tasks of the research are: analysis of the fairy tale as a literary genre, as a linguistic text and as a methodological tool and some features of foreign language learning for adults, in this case for students. From a theoretical and methodological point of view, there are detailed statements of German-speaking linguists and specialists in the field of teaching a foreign language, and from a practical point of view, the development is based on the teaching of Bulgarian as a foreign language for students at the Institute of Slavic Studies at the University of Jena “Friedrich Schiller” in Germany and at the Baku Slavic University in Azerbaijan. The general conclusions of the study indicate that the use of the fairy tale in the process of foreign language learning is undoubtedly both a very successful and no less interesting tool. What is innovative in this research is the focus on the age group of the participants in the foreign language process – the students, who are adult participants. In this sense, the tale reveals additional possibilities and ideas for application, which would contribute both to the practical learning process of foreign languages in general, but also to theoretical scientific disciplines, such as linguistics, methodology of teaching foreign languages, lexicology, foreign studies of the countries whose language is taught, sociolinguistics and so on.